The impact of strategic capabilities in achieving sustainable competitive advantage - Neamah Hattab, Helen; Mutter Atti, Liqaa; Oudah Sabeeh, Afrah (South Asian Journal of Social Sciences and Humanities, 2023)
The research aims at the impact of strategic capabilities as an independent variable through its dimensions (technical knowledge to build value, the ability to generate and own resources, and the technology used) on the sustainable competitive advantage as a dependent variable and its dimensions (Cost, quality, delivery, flexibility) The research topics are among the current issues aimed at helping companies discover and build strategic capabilities that support the researched company in a confrontation between competing companies and the ability of the studied company to stabilize and ensure success, excellence and creativity. The researchers used the questionnaire as the primary tool for collecting Data related to the selection of a random sample of (95) respondents to analyze and display the responses of the sample members and their perceptions of the study variables and their sub-dimensions and to test the study hypotheses using descriptive and inferential statistical methods, as well as the use of field observations and personal interviews as aids in data collection. The researchers relied on statistical programs (16. SPSS V.25, Excel V) in processing and analyzing data by using the most appropriate statistical methods. The researchers reached a set of results, the most important of which is the existence of a relationship and the effect of the correlation between the independent variable, strategic capabilities and its dimensions, and the dependent variable, the sustainable competitive advantage and its dimensions. This means that sustainable competitive advantages derive the ingredients for achieving them from the components of the services provided by the researched company. Whenever the research sample companies possess the technical knowledge to build value in the presentation in delivering products and services to customers, whenever they can achieve sustainable competitive advantages within their work environment.
Keywords: strategic capabilities; competitive advantage; sustainability; fertilizer companies